Alzheimer’s Disease–Thrombosis Comorbidity: A Growing Body of Evidence from Patients and Animal Models - Joanna Koch-Paszkowski; Christopher Sennett; Giordano Pula (Cells)
Background/Objectives: A growing body of evidence is amassing in the literature suggesting a correlation between Alzheimer’s disease (AD) and thrombotic vascular complications, which led to the suggestive hypothesis that thrombosis may contribute to AD onset and progression by damaging the neurovasculature and reducing the cerebral blood flow. In turn, low cerebral blood flow is likely to contribute to neurodegeneration by reducing nutrient and oxygen supply and impairing toxic metabolite removal from the brain tissue. Methods: We searched the literature for studies in animal models of AD or patients diagnosed with the disease that reported circulating markers of platelet hyperactivity or hypercoagulation, or histological evidence of brain vascular thrombosis. Results: Platelet hyperactivity and hypercoagulability have been described in multiple animal models of AD, and histological evidence of neurovascular thrombosis has also been reported. Similarly, clinical studies on patients with AD showed circulating markers of platelet hyperactivity and hypercoagulation, or histological evidence of neurovascular thrombosis collected from post-mortem brain tissue samples. Conclusions: Taken together, a convincing picture is emerging that suggests a strong correlation between systemic or neurovascular thrombosis and AD. Nonetheless, a mechanistic role for haemostasis dysregulation and neurovascular damage in the onset or the progression of AD remains to be proven. Future research should focus on this important question in order to clarify the mechanisms underlying AD and identify a treatment for this disease.